1995
DOI: 10.1093/oxfordjournals.humrep.a135804
|View full text |Cite
|
Sign up to set email alerts
|

Human chorionic gonadotrophin and steroid concentrations in follicular fluid: the relationship to oocyte maturity and fertilization rates in stimulated and natural in-vitro fertilization cycles

Abstract: The study investigates the relationship of follicular fluid steroids and human chorionic gonadotrophin to oocyte maturity and fertilization rates in stimulated and natural cycles. Oestradiol, progesterone, testosterone and human chorionic gonadotrophin were quantified in 129 samples of follicular fluid and the progesterone:oestradiol ratio calculated. Both stimulated cycles (short and long luteinizing hormone-releasing hormone/human menopausal gonadotrophin regimens) and natural cycles were compared. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 0 publications
2
23
0
Order By: Relevance
“…Uehara et al (29) and Hartshorne et al (30) did not find any relationship, while Enien et al reported higher P/E 2 ratios in follicles yielding successfully fertilized oocytes (31).…”
Section: Discussionmentioning
confidence: 91%
“…Uehara et al (29) and Hartshorne et al (30) did not find any relationship, while Enien et al reported higher P/E 2 ratios in follicles yielding successfully fertilized oocytes (31).…”
Section: Discussionmentioning
confidence: 91%
“…It has been suggested that estradiol-17β and progesterone might be markers of the level of oocyte maturity and fertilization [22,23]. However, some previous studies found no correlation between oocyte maturity and the concentrations of estradiol-17β and progesterone in FF [24,25]. Consequently, there is no agreement concerning the relationship between ovarian steroid hormones and oocyte maturation.…”
Section: Discussionmentioning
confidence: 99%
“…R5020’s ability to stimulate P4 secretion is observed at concentrations equal to or greater than 16 μM. While 16 μM may appear to be a pharmacological dose, it is within the physiological range, since women undergoing either natural or gonadotropin-stimulated cycles have P4 follicular fluid levels between 15 to 60 μM (Enien, et al 1995, Kamel, et al 1994, Tarlatzis, et al 1993). However, human PGRMC1 binds R5020 with high affinity (EC 50 of ≈ 10 nM; Figure 2A; (Peluso, et al 2009).…”
Section: Introduction and Historical Perspectivementioning
confidence: 99%